Detergent free protein extraction protocols for white adipose tissue from halal meat - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri , Nor Azwani (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Obesity is defined as an increase in the size of fat mass being a major health problem around the global and is associated with the development of type 2 diabetes mellitus. The rapidly increasing prevalence of these diseases poses a challenging healthcare burden in terms of the associated mortality, morbidity, and economic impact. Thus, prevention and treatment of these diseases require targeting their underlying mechanism. White adipose tissues are an important endocrine tissue which not only works as a reservoir of fat but also secrete various kinds of hormones (bioactive peptides or protein). Some of them are beneficial for human health and important for the utilization of the consumed energy and some are negatively correlated to obesity and diabetes. The objective of this study was to extract the total protein from halal meat sources i.e. chicken, beef and lamb adipose tissues using detergent free protocol. Abdominal adipose tissues were removed from chicken, beef and lamb, then rinsed with ice-cold phosphate-buffered saline (PBS) solution. Delipidation of aforementioned tissue lysates was prepared by chloroform/methanol extractions modified from Bligh and Dyer. Then, protein concentration was assessed using Protein Assay Bicinchoninate Kit (Nacalai Tesque, Japan). The experiment was conducted in triplicates and the results are presented as means ± SD. Preliminary results indicate that the extraction of 10 gram subcutaneous adipose tissues from chicken, beef and lamb yielded about 0.1 gram of protein amount which was only 1 % from the total tissue mass. The protein concentration in fats from chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml respectively. Adipose tissue contains a relatively smaller percentage of protein by weight. Thus, the success of protein extraction protocols depends on the extraction of as much protein as possible from fat samples. The protein extraction from wasted adipose tissues in meat sources may be useful enrichment sources for health conditions.